Performance analysis of local brand organic cosmetics marketing as an effort to develop the Jambi regional economy - Musnaini Musnaini; Lilis Suryani; Muhammad Irsyad; Asrini Asrini; Ida Ketut Mudhita (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2022)
This study aims to explain regional economic growth from the perspective of the mediating role of the brand image between brand trust and marketing performance of local organic-based cosmetic products as a sustainable new business model for strengthening Jambi regional economic growth. A regional economic growth model based on marketing performance with brand image and mediated by brand trust in startup businesses. The test evidence shows that: (1). directly brand trust has a positive and significant effect on brand image and marketing performance (2) the direct effect of brand trust on brand image is greater than the effect on marketing performance. (3) The indirect effect shows that brand trust in marketing performance through brand image is significantly positive. (4) brand image partially mediates between brand trust and marketing performance for new local product businesses as a strengthening of sustainable regional economic growth.